Health actions in primary care to reduce child mortality - Camila Marques Careti; Maria Cândida de Carvalho Furtado; Janaína Costa Barreto; Jéssica Batistela Vicente; Poliana Raimundini de Lima (Universidade Federal do Ceará, 2016)
Objective: to identify the health actions aimed at reducing child mortality in primary care in a county of São Paulo, Brazil. Methods: an exploratory study with a quantitative approach. 54 health professionals (nurses, doctors and community health agents) participated in this study in three health units selected. Results: most participants reported to develop actions to encourage breast-feeding; of the children assisted, 59.3% had their vaccination updated; 72.2% of doctors and nurses confirmed that the children have at least one appointment in their first week of life. For planning in health care, 51.9% reported that sometimes there is health team participation in the meetings. Conclusion: several actions correspond to those recommended by the child-care public policies. However, there are weaknesses pointing at the need to enhance the vision of the health professionals for greater planning, adapting to the needs of the child population in order to reduce the deaths.